Analysis of the Implementation of Halal Principles in the Food Industry in Indonesia: Challenges and Opportunities - Ubaidillah, Firqi (STAI AN-NAJAH INDONESIA MANDIRI, 2024)
This research explores the application of halal principles in the food industry in Indonesia, highlighting the challenges and opportunities faced by industry players. Indonesia, as the country with the largest Muslim population in the world, faces unique dynamics in developing a halal food ecosystem. The main challenges include the high cost of halal certification, complex administrative procedures, and manufacturers' lack of understanding of halal standards, especially among SMEs. Meanwhile, increasing consumer awareness of the importance of halal food provides great opportunities for producers to innovate and expand markets, both at the domestic and international levels. This research identifies the need for supportive policies, including subsidies for halal certification and training programs for producers, as well as the importance of education-based marketing strategies to increase consumer confidence in halal products. With close collaboration between the government, industry players and consumers, the halal food industry in Indonesia has the potential to grow sustainably and compete in the global market. Keywords: halal food, halal certification, SMEs, consumer behavior, innovation, marketing strategy